2021
DOI: 10.1371/journal.pone.0252807
|View full text |Cite
|
Sign up to set email alerts
|

Do oral contraceptives affect young women’s memory? Dopamine-dependent working memory is influenced by COMT genotype, but not time of pill ingestion

Abstract: Background Despite the widespread use of oral contraceptives (OCs), and the well-documented influence of estrogens, notably 17β-estradiol (E2), on cognition, research relating OCs to working memory is limited and mixed. Two factors may contribute to these mixed findings: 1) pharmacokinetics of oral contraceptives, which drive fluctuations in synthetic hormone levels; and 2) genetic polymorphisms related to dopamine degradation and working memory, which interact with E2. This research investigated whether the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 47 publications
0
8
0
Order By: Relevance
“…), different doses and type of progestin administered, and/or duration of treatment (Gogos et al, 2014;Pletzer and Kerschbaum, 2014;Warren et al, 2014). Moreover, genotype might be another important variable to consider when examining cognitive function in hormonal contraceptives' users (Gravelsins et al, 2021). Likewise, we cannot rule out the possibility that different doses or type of synthetic steroids used in hormonal contraceptives might alter cognitive abilities in rats; moreover, strain and/or species differences might also contribute to the actions of EE and LNG on cognition.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…), different doses and type of progestin administered, and/or duration of treatment (Gogos et al, 2014;Pletzer and Kerschbaum, 2014;Warren et al, 2014). Moreover, genotype might be another important variable to consider when examining cognitive function in hormonal contraceptives' users (Gravelsins et al, 2021). Likewise, we cannot rule out the possibility that different doses or type of synthetic steroids used in hormonal contraceptives might alter cognitive abilities in rats; moreover, strain and/or species differences might also contribute to the actions of EE and LNG on cognition.…”
Section: Discussionmentioning
confidence: 97%
“…), type of progestin administered, different dose of EE used, and/or duration of treatment (Beltz et al, 2015;Gogos et al, 2014;Pletzer and Kerschbaum, 2014;Warren et al, 2014;Wharton et al, 2008). Either improvement (Gurvich et al, 2020;Plamberger et al, 2021;Rosenberg and Park, 2002), no difference (Gogos, 2013;Gravelsins et al, 2021;Islam et al, 2008;Mihalik et al, 2009;Mordecai et al, 2008;Rosenberg and Park, 2002), or deterioration (Griksiene et al, 2018;Griksiene and Ruksenas, 2011) in cognitive abilities, have been reported in hormonal contraceptives' users compared to naturally cycling women.…”
Section: Introductionmentioning
confidence: 99%
“…In 7 studies, cognitive task performances were compared between OC and NC groups in different cycle phases: menses, follicular and luteal phases in 3 studies, menses and follicular phases in one study, luteal and menses phases in 2 studies, follicular, and luteal in one study. Only Mordecai et al (2008) indicated randomizing the test sessions depending on the phases of the menstrual cycle whereas Gravelsins et al (2021) counterbalanced the order of the sessions for both the OC and NC groups. Six studies tested for actual levels of hormones to ensure that the phases of the menstrual cycle were adequately defined and to compare levels of hormones between NC women and OC users.…”
Section: Resultsmentioning
confidence: 99%
“…Conditions of OC intake. Previous research suggests that certain conditions of OC use, such as age at first use or whether OC were taken before or after the measurement, may be important (Anderl et al, 2022; Gravelsins et al, 2021). In our sample, participants did not differ in their approach and avoidance behaviors depending on whether they started taking OC as adolescents (aged younger than 18 years (N=42)) or as adults (aged older than 18 years (N=22)) (no interaction of stress x emotion x movement x onset: F (1,62) = 0.997, p = .322, η 2 ρ = 0.016), nor did the timing of daily intake (before or after measurement) make a difference (no interaction of stress x emotion x movement x time of OC intake: F (1,62) = 2.6674, p = .107, η 2 ρ = 0.041).…”
Section: Resultsmentioning
confidence: 99%